Surface Polishing with Flexible Link Manipulators - Pfeiffer, F. (2012)
A position and force control concept for a manipulator with elasticity in joints and links is developed. The manipulator is modelled as a multibody system with distributed parameters. The control concept is performed in three steps. At first, a suitable cartesian reference path for the flexible robot is generated taking into account its high demand for a smooth trajectory. Secondly, the corresponding joint trajectories for the rigid robot including all restrictions are generated. Then, path tracking is improved by regarding the elastic influences of all links and joints. Thirdly, a control loop is added which feeds back joint positions/velocities and strain gauge measurements at the elastic arms in order to reduce trajectory deviations and damp remaining oscillations. The simultaneous position/force control is obtained due to the manipulator flexibility which acts as a force measuring unit. This control strategy is experimentally applied to a five-DOF flexible laboratory robot to polish a plane surface.